2010
DOI: 10.1177/1077801210387747
|View full text |Cite
|
Sign up to set email alerts
|

False Allegations of Sexual Assault: An Analysis of Ten Years of Reported Cases

Abstract: One of the most controversial disputes affecting the discourse related to violence against women is the dispute about the frequency of false allegations of sexual assault. In an effort to add clarity to the discourse, published research on false allegations is critiqued, and the results of a new study described. All cases (N = 136) of sexual assault reported to a major Northeastern university over a 10-year period are analyzed to determine the percentage of false allegations. Of the 136 cases of sexual assault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(123 citation statements)
references
References 17 publications
3
118
1
1
Order By: Relevance
“…Moreover, based on an estimated 12 percent of student victims reporting to the police (Kilpatrick, 2007) and 6 percent of police reports involving false allegations (Lisak et al 2010 We view these results as contributing to a more complete understanding of the non-pecuniary costs associated with college football. Moreover, by documenting how specific contexts modify the effects of football games on the incidence of rape, and what types of rapes are affected most, our results can inform awareness and prevention efforts.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, based on an estimated 12 percent of student victims reporting to the police (Kilpatrick, 2007) and 6 percent of police reports involving false allegations (Lisak et al 2010 We view these results as contributing to a more complete understanding of the non-pecuniary costs associated with college football. Moreover, by documenting how specific contexts modify the effects of football games on the incidence of rape, and what types of rapes are affected most, our results can inform awareness and prevention efforts.…”
Section: Discussionmentioning
confidence: 91%
“…A baseless case is a case that does not meet the legal criteria for the crime [9]. Thus, also if the classification process is flawless then some proportion of cases would still not be false allegations in the sense that the complainant deliberately tried to mislead everyone.…”
Section: The Unfound Category and The New Policymentioning
confidence: 99%
“…Rumney [4] concluded that because of methodological problems it is impossible to use the studies that were reviewed to estimate the true prevalence rate of false allegations of rape. The controversy concerning the prevalence of false allegations persists [8][9][10]. …”
mentioning
confidence: 99%
“…False accusations have been repeatedly shown to be rare (e.g. Lisak et al 2010) and yet most processes seem to be set up to protect against them more than to support victims. If you take one thing away from this article it's this: if a young astronomer comes to you with a story of harassment, you should not in that moment express doubt, nor ask for any proof, but instead trust the process to find the truth and offer your support and sympathy.…”
Section: Sexual Harassmentmentioning
confidence: 99%